2018
DOI: 10.1093/eurheartj/ehy233
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of the GRACE score by 2-hour post-load glucose improves prediction of long-term major adverse cardiac events in acute coronary syndrome in patients without known diabetes

Abstract: Two-hour PG, but not FPG, is an independent predictor of adverse outcome after ACE even after adjusting for the GRS. Two-hour PG, but not FPG, improves the predictability of prognostic models containing GRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 46 publications
0
32
1
Order By: Relevance
“…3,14 We have reported that 2h-PG was a better determinant of post-MI prognosis than FPG or APG. 13,21 In the EUORASPIRE IV 20 and Silent Diabetes Study, 27 2h-PG, but not FPG or HbA1c, was related to prognosis. The 2h-PG, but not the FPG, was associated with adverse post-MI prognosis in patients with pDM in this.…”
Section: Discussionmentioning
confidence: 98%
“…3,14 We have reported that 2h-PG was a better determinant of post-MI prognosis than FPG or APG. 13,21 In the EUORASPIRE IV 20 and Silent Diabetes Study, 27 2h-PG, but not FPG or HbA1c, was related to prognosis. The 2h-PG, but not the FPG, was associated with adverse post-MI prognosis in patients with pDM in this.…”
Section: Discussionmentioning
confidence: 98%
“…The 2hPG also improved the predictability of the Global Registry of Acute Coronary Events (GRACE) risk score. 169 Unfortunately, HbA1c was not included in this study. In the present study, 2hPG indicating IGT (n=1,242) was significantly associated with the primary endpoint, while the 2hPG indicating T2DM (n=435) showed a similar trend with borderline statistical significance, probably due to the lack of power, given the results of previous studies.…”
Section: Prognostic Implications Of Indicators Of Dysglycaemiamentioning
confidence: 99%
“…Among common cardiovascular risk factors, type 2 diabetes and its preceding state, impaired glucose tolerance (IGT), designated together as dysglycemia, increase the risk for CVD by two to four times (2). Moreover, future morbidity and mortality of patients with coronary artery disease (CAD) is considerably higher in the presence of dysglycemia, including newly detected glucose perturbations (3)(4)(5). Nonetheless, type 2 diabetes and IGT remain unrecognized in approximately two-thirds of coronary patients (6,7).…”
mentioning
confidence: 99%